Pemerolehan Kata Pada Anak TK Fase Fondasi - Sarifatul Jannah; Aisyah Aisyah; Ira Datul Aini; Qurratu A yun; Hodairiyah Hodairiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze word acquisition in kindergarten children at the foundation phase aged 4–5 years. The approach used in this research is a qualitative approach with a qualitative descriptive method. The data sources were kindergarten children aged 4–5 years in Saroka Village, Saronggi District, Sumenep Regency, East Java. Data collection was conducted through interview techniques using picture media in the form of fruits (apple and watermelon) and animals (cow and chicken). The data obtained consisted of word utterances produced by children in response to the picture stimuli. The results showed that (1) most children were able to name the objects in the pictures correctly, indicating that children had prior language experience from their surrounding environment; (2) the use of picture media proved effective in helping children recognize and recall vocabulary they had mastered; (3) there were variations in word acquisition abilities among children influenced by internal factors (age, cognitive maturity, interest, motivation, and health) as well as external factors (social environment and socioeconomic status). This study concludes that word acquisition in kindergarten children at the foundation phase occurs uniquely for each individual and is highly influenced by environmental stimulation. Picture media can be an effective means to support children's vocabulary development, so teachers and parents need to provide varied and contextual language stimulation to optimize children's early language development.